2007
DOI: 10.1002/chem.200601330
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Natural Polyoxygenated Cyclohexanes and Cyclohexenes from [(p‐Tolylsulfinyl)methyl]‐p‐quinols

Abstract: Exploitation of the beta-hydroxysulfoxide fragment present in a number of enantiomerically pure (SR)- and (SS)-[(p-tolylsulfinyl)methyl]-p-quinols allowed chemo- and stereocontrolled conjugate additions of different organoaluminium reagents to the cyclohexadienone moiety. The same fragment was also shown to act as an efficient chiral masking carbonyl group, after oxidation to sulfone and retroaddition in basic medium, with elimination of methyl p-tolyl sulfone. Through the use of both transformations as key st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…When this sequence of reactions was applied to (4 S )‐ 6 , the dextrorotatory enantiomer of epiepoformin was furnished, [ α ] D = +315 ( c = 1.1, EtOH) 28. The conversion of (+)‐epiepoformin into (–)‐theobroxide and (+)‐4‐epigabosine A was described previously 23b…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When this sequence of reactions was applied to (4 S )‐ 6 , the dextrorotatory enantiomer of epiepoformin was furnished, [ α ] D = +315 ( c = 1.1, EtOH) 28. The conversion of (+)‐epiepoformin into (–)‐theobroxide and (+)‐4‐epigabosine A was described previously 23b…”
Section: Resultsmentioning
confidence: 99%
“…Formally, regioselective hydrolysis of the epoxide in (+)‐epiepoformin or (–)‐epoformin could deliver (+)‐gabosine A, whereas the corresponding antipode, which is equally available through our approach, would deliver the naturally occurring enantiomer. However, it was described that hydrolysis of the epoxide in epiepoformin was a troublesome transformation that could only be achieved by treatment with aqueous sodium acetate in 45 % yield;23b furthermore, this reaction delivered 4‐epigabosine A, an epimer of the natural product. In view of this precedent, for the synthesis of gabosine A, we decided to assay the hydrolysis of the epoxide with a former intermediate lacking the conjugated C–C double bond; it was thought that the higher flexibility could benefit the desired transformation.…”
Section: Resultsmentioning
confidence: 99%
“…We found this transformation to be completely diastereoselective, and an X-ray diffraction study [58] of the product confirmed our hypothesis regarding the facial selectivity, as the hydride was delivered to the convex face. An analogous reaction occurs when 2a is treated with AlMe 3 , affording the 1,2-addition product (Scheme 3) [5963]. …”
Section: Resultsmentioning
confidence: 99%
“…In Carreño's synthesis of (+)-epiepoformin (2) and (-)theobroxide (21) [112,113] the key step involved a stereocontrolled conjugated addition of trimethylaluminium to a chiral sulfoxide-pquinol [114] in order to introduce the required asymmetry (scheme 25). p-Benzoquinone dimethylmonoacetal (163) reacted with the lithium anion of (R)-methyl-p-tolylsulfoxide, and then was subjected to hydrolysis of the acetal to afford sulfoxide 164.…”
Section: Carreño's Methodologymentioning
confidence: 99%